A New Analytical Modeling Method For Photovoltaic Solar Cells Based On Derivative Power Function - Zieba Falama, R.; Dadjé, A.; Djongyang, N.; Doka, S.y. (University of Eloued جامعة الوادي, 2016)
This paper presents a simple method of optimizing the photovoltaic (PV) generator based on the one diode electrical model. The method consists in solving a second degree equation representing the derivative of the power function. The maximum current and voltage are determined, and the maximum power is deduced. Two popular types of photovoltaic panels constructed with different materials have been considered for the test: the multi-crystalline silicon (Shell S75), and the mono-crystalline silicon (Shell SP70). For various environmental conditions, a comparative study is done between the simulated results and the product manufacturer data. The obtained results prove the efficiency of the proposed method.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 02
Keywords: Model; Photovoltaic generator; Power function; Optimizing, Maximum power.